TEXT MINING - Todjiyeva Dilfuza Abdusalomovna, Haydarova Ozodaxon Adhamjon qizi, Kamoliddinova Odinaxon Abdukarim qizi, Mamasoliyeva Dilnoza Baxtiyor qizi (Journal Park Publishing, 2023)
It is a science about the generalized language of informatics, which appeared on the basis of the methods of machine learning and the rules of statistics . Text mining (also called text analytics ) is the use of natural language processing (NLP) to analyze free (unstructured) text in documents and databases or transform it into normalized, structured data suitable for machine control. artificial intelligence (AI) technology. learning (ML) algorithms.In our independent work, we provide an introduction to these technologies and highlight some of the features that contribute to an efficient solution.
Keywords: Text Analytics, Textmining, Deep Analytics, Descriptive Analytics, Predictive Analytics, Prescriptive Analytics, Diagnostic Analytics, NLP, Business Intelligence, Sentiment Analysis.